The Effectiveness of Tax Socialization through Digital Media: The Perspective of Millennial Taxpayers - Nasir, Nasir (Santoso Academy Network, 2025)
This research aims to explore the effectiveness of tax socialization through digital media, focusing on the perspective of millennial taxpayers. The development of digital technology provides a great opportunity to increase tax awareness, but its effectiveness in reaching and motivating millennials is still a question. This research uses a qualitative method with data collection techniques through interviews, observations, and documentation. The subject of the study is millennial taxpayers who actively use social media and tax applications. The results of the study show that although digital media is very popular among millennials, tax socialization conveyed through social media is still less relevant and personalized. Many millennial taxpayers want information that is more practical and directly related to their daily lives. In addition, existing tax applications are considered difficult to use, which hinders the effectiveness of information delivery. Therefore, it is necessary to improve the delivery of tax materials with a more interactive and creative format, as well as improve the tax application interface to make it more user-friendly. This research is important to provide input in designing a more effective tax socialization strategy for the millennial generation, in order to increase tax compliance in the future.